2003
DOI: 10.1038/nature01363
|View full text |Cite
|
Sign up to set email alerts
|

Human and bacterial oxidative demethylases repair alkylation damage in both RNA and DNA

Abstract: Repair of DNA damage is essential for maintaining genome integrity, and repair deficiencies in mammals are associated with cancer, neurological disease and developmental defects. Alkylation damage in DNA is repaired by at least three different mechanisms, including damage reversal by oxidative demethylation of 1-methyladenine and 3-methylcytosine by Escherichia coli AlkB. By contrast, little is known about consequences and cellular handling of alkylation damage to RNA. Here we show that two human AlkB homologu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
662
0
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(701 citation statements)
references
References 25 publications
25
662
0
7
Order By: Relevance
“…ABH1 can demethylate single‐stranded DNA and RNA in vitro with low efficiency, with a preference for oxidation of N3‐methylcytosine (m 3 C) (Westbye et al , 2008), and has been suggested to act as histone demethylase and abasic site lyase (Müller et al , 2010; Ougland et al , 2012). While the homologous E. coli AlkB cannot oxidise m 5 C in vitro (Li et al , 2010) and human ALKBH2 and ALKBH3 preferentially repair alkylation at nucleobase heteroatoms such as m 3 C and 1‐methyladenosine (m 1 A) (Aas et al , 2003; Falnes et al , 2004), the oxidation of m 5 C involves transformation of a pseudobenzylic methyl group. In DNA, this reaction is catalysed by related Fe(II)/α‐ketoglutarate‐dependent oxygenases of the TET enzyme family, and the oxidation products play a significant role in epigenetic regulation in mammals (Tahiliani et al , 2009; Breiling & Lyko, 2015; Li et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…ABH1 can demethylate single‐stranded DNA and RNA in vitro with low efficiency, with a preference for oxidation of N3‐methylcytosine (m 3 C) (Westbye et al , 2008), and has been suggested to act as histone demethylase and abasic site lyase (Müller et al , 2010; Ougland et al , 2012). While the homologous E. coli AlkB cannot oxidise m 5 C in vitro (Li et al , 2010) and human ALKBH2 and ALKBH3 preferentially repair alkylation at nucleobase heteroatoms such as m 3 C and 1‐methyladenosine (m 1 A) (Aas et al , 2003; Falnes et al , 2004), the oxidation of m 5 C involves transformation of a pseudobenzylic methyl group. In DNA, this reaction is catalysed by related Fe(II)/α‐ketoglutarate‐dependent oxygenases of the TET enzyme family, and the oxidation products play a significant role in epigenetic regulation in mammals (Tahiliani et al , 2009; Breiling & Lyko, 2015; Li et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was also predicted then that certain members of the AlkB family were likely to demethylate m 6 A in RNA 96. Subsequently, such demethylation of m 6 A in RNA was indeed observed to be the mechanism for resetting methyl marks generated by N 6 A RNA MTases 68, 99. Oxidation of the methyl group by these enzymes results in formation of N 6 hmA and N 6 fA, which restore the original base, releasing formaldehyde and formate 100.…”
Section: How Are M6a Marks Reset?mentioning
confidence: 98%
“…m 1 A has recently been discovered as another mRNA modification, in addition to m 6 A, pseudouridine, and m 5 C. The presence of m 1 A at the 5′ UTR region in mRNA has been suggested to promote translation (Dominissini et al, 2016;Li et al, 2016). ALKBH3, a DNA repair enzyme that demethylates N 1 -methyldeoxyadenosine in single-stranded DNA (Aas et al, 2003;Duncan et al, 2002) has been suggested as a potential demethylase of m 1 A in mRNA , the functional relevance of which still requires further investigations. ALKBH3 is also capable of repairing tRNA alkylation damages (Aas et al, 2003), again the biological relevance of which was not clear.…”
Section: Trna M 1 a Demethylation By Alkbh1mentioning
confidence: 99%
“…ALKBH3, a DNA repair enzyme that demethylates N 1 -methyldeoxyadenosine in single-stranded DNA (Aas et al, 2003;Duncan et al, 2002) has been suggested as a potential demethylase of m 1 A in mRNA , the functional relevance of which still requires further investigations. ALKBH3 is also capable of repairing tRNA alkylation damages (Aas et al, 2003), again the biological relevance of which was not clear. We show that m 1 A in tRNA is the main substrate of ALKBH1.…”
Section: Trna M 1 a Demethylation By Alkbh1mentioning
confidence: 99%